Analisis Daya Dukung Sumber Daya Lahan dan Air di Sarilamak, Kabupaten Lima Puluh Kota: Analysis of Land and Water Resource Carrying Capacity in Sarilamak, Lima Puluh Kota District - Fitrada, Wathri; Rahmania, Syiffa; Ekawaty, Reni; Harmailis (Universitas Jambi, 2026)
Environmental carrying capacity is a vital indicator in spatial planning and food and water security. The objective of this study was to assess the status of land carrying capacity (LCC) and water carrying capacity (WCC) in Nagari Sarilamak, Harau District, Lima Puluh Kota Regency. The analysis is based on PermenLH No. 17/2009. It used a quantitative descriptive approach. This approach was based on secondary data and QGIS spatial analysis. The analysis was used to calculate the weighted runoff coefficient of land cover. Field validation was conducted to confirm the actual conditions. The results are clear: land carrying capacity has a surplus. This means that the availability of rice fields exceeds the population's rice consumption needs. Water carrying capacity, however, was found to be in deficit, despite relatively high annual rainfall. This was attributed to an uneven spatial and temporal distribution of water, as well as increased runoff due to changes in land cover. This imbalance requires integrated management through conservation of catchment areas, rainwater harvesting, and control of land use change. This study makes clear methodological and practical contributions to spatial planning based on environmental carrying capacity at the village level.